HEGEMONI DALAM NOVEL MARYAM KARYA OKKY MADASARI: KAJIAN HEGEMONI GRAMSCI - Dwi Safitri; Siti Fatimah; R. Yusuf Sidiq Budiawan (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
This research aims to describe the hegemony of power in the novel "Maryam" by Okky Madasari using the Gramscian hegemony approach. The research employs a qualitative descriptive method, focusing on the analysis of power hegemony in the novel through Gramsci's theory. Data collection is conducted through documentation methods. Data analysis involves data reduction, presentation of analysis results, and drawing conclusions. The research findings reveal various forms of power hegemony in the novel. The police force exercises hegemonic control through violence against the characters of Maryam's family and the residents of Gegerung. Maryam herself experiences hegemony from Mother Alam, while the beliefs held by Maryam's family and the people of Gegerung are considered unacceptable by other communities. The power depicted in the novel achieves leadership through oppression and is expected to be unsustainable due to its detrimental nature to other characters. Furthermore, there is a shift in power dynamics within the novel. The hegemonized characters eventually reach an agreement to accept the treatment from those in power, indicating a dynamic change in power within the narrative.